Analisis Kelayakan Usahtani Kakao (Theobroma Cacao L) Di Kecamatan Wanasaba - Melina Melina Hidayah (Journal of Agri Rinjani: Social Agricultural Economics - Faculty of Agriculture, UGR, 2022)
Cocoa is one of the mainstay commodities of plantations whose role is quite essential for the national economy, and plantation commodities have an accurate and reliable role in realizing agricultural development programs. Wanasaba District is one of the sub-districts in East Lombok Regency, which has the potential for the development of cocoa farming. This research was conducted in Wanasaba District, East Lombok Regency. The method used in this research was the R/C/Ratio analysis method. The results of this study showed that the cost of cocoa farming income was Rp. 1,537,540/LLG with an average/ha of Rp. 4,021,465 indicates that cocoa farming in Wanasaba District, East Lombok Regency is feasible, with the R/C ratio of 1.2.